Badania ratownicze przeprowadzone w 1998 r. na stanowisku 16 Łódź-Polesie. Osada kultury łużyckiej z IV okresu epoki brązu - Zawilski, Paweł (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
Examinations of the described object were undertaken because of building works carried out on the ground neighbouring the Łódź ZOO, that is at the site of a Lusatian Culture settlement from the IV th and V th phase of the Bronze Age. The site had been explored by the workers without archaeological supervision until the final stage of building works. Excavations resulted in recovering and registration of 6 dwelling pits and a cultural layer of the mid-Poland Lusatian culture group. Only the object no. 6 has been preserved in its greatest part. The remaining objects were devoid of full outline and higher layers of the filling. The object no. 6 was most probably a household object of a semi- sunken hut type. In spite of a large size of the object on the level on which it was distinguished (302 by 160 cm), its size reaches only 250 x 160 cm at the bottom level, what excludes its dwelling character. Presumably it was a storage object. During exploration, in the western part of the cave, a readable filling was observable, clearly distinguishing from the rest of the object (by a light brown colouring). It reflected axially the outline of the object and occupied 1/3 of its surface. A borderline between its two parts ran across the pit. May be we deal here with the case of traces of inner division, the objective of which was to isolate part of stored products or articles. The shallower part of the pit, situated on the opposite side, may be interpreted as a stair enabling entering the object. The relic material includes fragments of ceramics and more rarely flint artefacts and pugging. Stylistics and technology in which the pottery was made allow to relate the examined site to the IV th phase of the Bronze Age.